2017
DOI: 10.3171/2016.7.jns161194
|View full text |Cite
|
Sign up to set email alerts
|

Early versus late arteriovenous malformation responders after stereotactic radiosurgery: an international multicenter study

Abstract: OBJECTIVE The goal of stereotactic radiosurgery (SRS) for arteriovenous malformation (AVM) is complete nidus obliteration, thereby eliminating the risk of future hemorrhage. This outcome can be observed within the first 18 months, although documentation of AVM obliteration can extend to as much as 5 years after SRS is performed. A shorter time to obliteration may impact the frequency and effect of post-SRS complications and latency hemorrhage. The authors' goal in the present study was to determine predictors … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
11
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 21 publications
(14 citation statements)
references
References 38 publications
3
11
0
Order By: Relevance
“…22,51,55 A literature review revealed that the most commonly reported factors associated with favorable outcome of SRS for AVMs were ruptured AVMs, lower AVM grade, smaller AVM volume, and a higher marginal dose. 11,19,52,[56][57][58][59] The present study showed that Spetzler-Martin grades I to III, AVM volumes 10 cc, and, more significantly, the appearance of perinidal T2 hyperintensity signal in post-SRS follow-up MRIs were independent predictors of AVM obliteration, which is consistent with other AVM SRS series. 11,19,22,52,[56][57][58][59][60] The importance of the MRI appearance of perinidal high T2 signal, after SRS of AVMs, in predicting nidal obliteration was highlighted by other investigators.…”
Section: Discussionsupporting
confidence: 91%
See 4 more Smart Citations
“…22,51,55 A literature review revealed that the most commonly reported factors associated with favorable outcome of SRS for AVMs were ruptured AVMs, lower AVM grade, smaller AVM volume, and a higher marginal dose. 11,19,52,[56][57][58][59] The present study showed that Spetzler-Martin grades I to III, AVM volumes 10 cc, and, more significantly, the appearance of perinidal T2 hyperintensity signal in post-SRS follow-up MRIs were independent predictors of AVM obliteration, which is consistent with other AVM SRS series. 11,19,22,52,[56][57][58][59][60] The importance of the MRI appearance of perinidal high T2 signal, after SRS of AVMs, in predicting nidal obliteration was highlighted by other investigators.…”
Section: Discussionsupporting
confidence: 91%
“…11,19,52,[56][57][58][59] The present study showed that Spetzler-Martin grades I to III, AVM volumes 10 cc, and, more significantly, the appearance of perinidal T2 hyperintensity signal in post-SRS follow-up MRIs were independent predictors of AVM obliteration, which is consistent with other AVM SRS series. 11,19,22,52,[56][57][58][59][60] The importance of the MRI appearance of perinidal high T2 signal, after SRS of AVMs, in predicting nidal obliteration was highlighted by other investigators. 19,22,60 Arrese Regańón et al 19 reported that the development of hyperintensity on T2 MRI after the treatment was among the strongest predictive factors of achieved nidal obliteration in 77% of their series of 59 radiosurgically treated AVMs.…”
Section: Discussionsupporting
confidence: 91%
See 3 more Smart Citations